2017
DOI: 10.5114/jcb.2017.68467
|View full text |Cite
|
Sign up to set email alerts
|

Is intraoperative real-time dosimetry in prostate seed brachytherapy predictive of biochemical outcome?

Abstract: PurposeTo analyze intraoperative (IO) dosimetry using transrectal ultrasound (TRUS), performed before and after prostate low-dose-rate brachytherapy (LDR-BT), and compare it to dosimetry performed 30 days following the LDR-BT implant (Day 30).Material and methodsA total of 236 patients underwent prostate LDR-BT using 125I that was performed with a three-dimensional TRUS-guided interactive inverse preplanning system (preimplant dosimetry). After the implant procedure, the TRUS was repeated in the operating room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Higher dose can deliver to prostate with lower exposure to organs at risks; 2. The treatment time became remarkably shorter than EBRT because usually the insertion was completed within one day [ 14 , 19 , 27 ]. In comparison with EBRT, LDR-BT can deliver a higher dose with lower exposure to organs at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Higher dose can deliver to prostate with lower exposure to organs at risks; 2. The treatment time became remarkably shorter than EBRT because usually the insertion was completed within one day [ 14 , 19 , 27 ]. In comparison with EBRT, LDR-BT can deliver a higher dose with lower exposure to organs at risk.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies compared stranded seeds to loose seeds [ 9 , 13 , 14 , 19 , 20 , 21 ], but few studies have compared the implant quality of linked seeds with that of loose seeds for prostate brachytherapy [ 17 , 22 , 23 , 24 , 25 ]; however, until now, there have been no reports about the plan reproducibility of linked seeds. Generally, intraoperative dosimetry based on ultrasound would not predict biochemical outcome [ 26 ]. Post-operative D 90 is an important dosimetric parameter for biochemical freedom from failure [ 27 ].…”
Section: Purposementioning
confidence: 99%
“…Recently, Taussky et al reported that intraoperative USD was predictive of Day 30 dosimetry but with low predictive power due to intraprostatic seed migration and other intraoperative factors that are unpredictable in USD, and biochemical recurrence-free rate was not dependent on any intraoperative USD dosimetry parameters (22). A few groups combined intraoperative CT with TRUS and performed intraoperative adaptive plan modification similarly as our approach, demonstrating improved prostate dose coverage and correlation with Day 30 (15, 23, 24) and Day 0 (15) dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies indicated some correlation between intraoperative USD and postoperative CT or CT/MRI dosimetry, there exists significant disparity between them (10, 1618), suggesting that current USD approach needs improvement to achieve optimal implant distribution (1922). Recently, Taussky et al reported that intraoperative USD was predictive of Day 30 dosimetry but with low predictive power due to intraprostatic seed migration and other intraoperative factors that are unpredictable in USD, and biochemical recurrence-free rate was not dependent on any intraoperative USD dosimetry parameters (22). A few groups combined intraoperative CT with TRUS and performed intraoperative adaptive plan modification similarly as our approach, demonstrating improved prostate dose coverage and correlation with Day 30 (15, 23, 24) and Day 0 (15) dosimetry.…”
Section: Discussionmentioning
confidence: 99%